An approach to difficult airway in infants: Comparison of GlideScope® Spectrum LoPro, GlideScope® Spectrum Miller and conventional Macintosh and Miller blades in a simulated Pierre Robin sequence performed by 90 anesthesiologists - Irouschek, Andrea; Moritz, Andreas; Kremer, Sven; Fuchte, Tobias; Danzl, Anja; Schmidt, Joachim; Golditz, Tobias (PLoS ONE, 2023)
BACKGROUND: Airway management can be challenging in neonates and infants. The Pierre Robin sequence (PRS) is a condition characterized by micrognathia, glossoptosis and airway obstruction. The airway management of these patients poses great challenges for anesthesiologists and pediatricians alike. To date, there has been no direct comparison of the hyperangulated GlideScope® Spectrum LoPro (GLP), the straight GlideScope® Spectrum Miller (GSM), a conventional Macintosh (MC) and a conventional Miller blade (ML) in patients with PRS. METHODS: For this purpose, 90 anesthesiologists (43 with limited experience, 47 with extensive experience) performed orotracheal intubation on an Air-Sim® Pierre Robin X manikin using GLP, GSM, MC and ML in randomized order. 'Time-to-vocal-cords', 'time-to-intubate', 'time-to-ventilate', the severity of oral-soft-tissue-trauma and the subjective evaluation of each device were recorded. RESULTS: A significantly faster and better view of the vocal cords and lower oral-soft-tissue-trauma was achieved using the GLP (p<0.001). Though, there were no significant differences in the 'time-to-intubate' or 'time-to-ventilate'. The highest intubation success rate was found with GSM and the lowest with GLP (GSM 100%, ML 97.8%, MC 96.7%, GLP 93.3%). When using the videolaryngoscopes, there were no undetected esophageal intubations but in six cases prolonged attempts of intubation (>120s) with the GLP. In the sub-group with extensive experience, we found significantly shorter intubation times for the GSM and ML. The GLP was the tool of choice for most participants, while the conventional MC received the lowest rating. CONCLUSIONS: Videolaryngoscopy leads to increased safety for the prevention of undetected esophageal intubation in the airway management in a PRS manikin. Hyperangulated blades may ensure a good and fast view of the vocal cords and low oral-soft-tissue-trauma but pose a challenge during the placement of the tube. Specific skills and handling seem to be necessary to ensure a safe tube placement with this sort of blades.
CRIS-Team Scopus Importer:2023-08-11

Comparison of glidescope core, C-MAC miller and conventional miller laryngoscope for difficult airway management by anesthetists with limited and extensive experience in a simulated Pierre Robin sequence: A randomized crossover manikin study - Moritz, Andreas; Holzhauser, Luise; Fuchte, Tobias; Kremer, Sven; Schmidt, Joachim; Irouschek, Andrea (PLoS ONE, 2021)
Background Video laryngoscopy is an effective tool in the management of difficult pediatric airway. However, evidence to guide the choice of the most appropriate video laryngoscope (VL) for airway management in pediatric patients with Pierre Robin syndrome (PRS) is insufficient. Therefore, the aim of this study was to compare the efficacy of the Glidescope® Core™ with a hyperangulated blade, the C-MAC® with a nonangulated Miller blade (C-MAC® Miller) and a conventional Miller laryngoscope when used by anesthetists with limited and extensive experience in simulated Pierre Robin sequence. Methods Forty-three anesthetists with limited experience and forty-three anesthetists with extensive experience participated in our randomized crossover manikin trial. Each performed endotracheal intubation with the Glidescope® Core™ with a hyperangulated blade, the C-MAC® with a Miller blade and the conventional Miller laryngoscope. “Time to intubate” was the primary endpoint. Secondary endpoints were “time to vocal cords”, “time to ventilate”, overall success rate, number of intubation attempts and optimization maneuvers, Cormack-Lehane score, severity of dental trauma and subjective impressions. Results Both hyperangulated and nonangulated VLs provided superior intubation conditions. The Glidescope® Core™ enabled the best glottic view, caused the least dental trauma and significantly decreased the “time to vocal cords”. However, the failure rate of intubation was 14% with the Glidescope® Core™, 4.7% with the Miller laryngoscope and only 2.3% with the C-MAC® Miller when used by anesthetists with extensive previous experience. In addition, the “time to intubate”, the “time to ventilate” and the number of optimization maneuvers were significantly increased using the Glidescope® Core™. In the hands of anesthetists with limited previous experience, the failure rate was 11.6% with the Glidescope® Core™ and 7% with the Miller laryngoscope. Using the C-MAC® Miller, the overall success rate increased to 100%. No differences in the “time to intubate” or “time to ventilate” were observed. Conclusions The nonangulated C-MAC® Miller facilitated correct placement of the endotracheal tube and showed the highest overall success rate. Our results therefore suggest that the C-MAC® Miller could be beneficial and may contribute to increased safety in the airway management of infants with PRS when used by anesthetists with limited and extensive experience.
CRIS-Team Scopus Importer:2021-05-07

Postoperative pain therapy with hydromorphone; comparison of patient-controlled analgesia with target-controlled infusion and standard patient-controlled analgesia A randomised controlled trial - Wehrfritz, Andreas; Ihmsen, Harald; Fuchte, Tobias; Kim, Michael; Kremer, Sven; Weiss, Alexander; Schüttler, Jürgen; Jeleazcov, Christian (European Journal of Anaesthesiology, 2020)
BACKGROUND The challenge of managing acute postoperative pain is the well tolerated and effective administration of analgesics with a minimum of side effects. The standard therapeutic approach is patient-controlled analgesia (PCA) with systemic opioids. To overcome problems of oscillating opioid concentrations, we studied patient-controlled analgesia by target-controlled infusion (TCI-PCA) as an alternative. OBJECTIVE To compare efficacy, safety and side effects of standard PCA with TCI-PCA for postoperative pain therapy with hydromorphone. DESIGN Single-blinded, randomised trial. SETTING University Hospital, Germany from December 2013 to April 2015. PARTICIPANTS Fifty adults undergoing cardiac surgery. INTERVENTIONS Postoperative pain therapy on the ICU was managed with intravenous (i.v.) hydromorphone and patients randomised to TCI-PCA with target plasma concentrations between 0.8 and 10 ng ml(-1), or PCA with bolus doses of 0.2 mg. Pain was regularly assessed using the 11-point numerical rating scale (NRS). Blood pressure, heart rate, oxygen saturation and cardiac output were continuously monitored, and adverse events were registered throughout the study. MAIN OUTCOME MEASURES NRS pain ratings, hydromorphone doses, haemodynamic effects and side effects. RESULTS NRS pain ratings, total doses of hydromorphone and haemodynamic data did not differ significantly between TCI-PCA and PCA. The number of bolus doses during PCA was significantly higher than the number of target increases during TCI-PCA (P = 0.006). The number of negative requests was also significantly higher during PCA than during TCI-PCA (P = 0.02). The respiratory rate on the first postoperative morning was 25 +/- 6 min(-1) during TCI-PCA, compared with 19 +/- 4 min(-1) during PCA (P = 0.022). Nausea occurred in 30% after TCI-PCA and 24% after PCA (P = 0.46). CONCLUSION TCI-PCA was effective and well tolerated in acute postoperative pain management after cardiac surgery. Further studies are needed to evaluate this approach in clinical practice.
CRIS-Team WoS Importer:2020-11-27